2016
DOI: 10.1177/2057158516637236
|View full text |Cite
|
Sign up to set email alerts
|

Home healthcare nurses’ experiences of being on stand by as a first responder in a ‘While Waiting For the Ambulance’ assignment

Abstract: The aim of the study is to describe experiences of the 'While Waiting for the Ambulance' (WWFA) assignment, as described by home healthcare nurses (HHCNs). Since the early 1990s, municipal resources in Sweden, preferably firefighters, have been dispatched on WWFA. In order to further assist the local residents on an island in the southwest of Sweden, HHCNs have recently begun accompanying firefighters on WWFA. A reflective lifeworld approach was used for data analysis including in-depth interviews with eight H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…Accordingly, earlier research suggests that developing professional competence and feeling qualified and confident when on duty require repeated training, education, reflection and feedback. 6,29,30 In fact, there is evidence that structured feedback, reflection and learning are all associated with competence in integrating theory and practice, building confidence at work, and positive changes for professional competence. 22,[31][32][33] The nurses in this study have a reflective attitude, which is connected to their strong will to develop professional competence as in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, earlier research suggests that developing professional competence and feeling qualified and confident when on duty require repeated training, education, reflection and feedback. 6,29,30 In fact, there is evidence that structured feedback, reflection and learning are all associated with competence in integrating theory and practice, building confidence at work, and positive changes for professional competence. 22,[31][32][33] The nurses in this study have a reflective attitude, which is connected to their strong will to develop professional competence as in earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…6 Earlier studies show that interprofessional teamwork increases the sphere of competence of nurses and enhances co-operation between professionals. 6,13 However, emotional issues can arise when nurses feel inadequate or anxious about their lack of understanding of what is expected in such assignments. In a previous study on HHNs' experiences of being on standby as first responders, the nurses reported that in order to feel safe in their professional role and in the unfamiliar situation, they needed support from other professionals in providing high-quality and safe patient care.…”
Section: Introductionmentioning
confidence: 99%
“…In a rural environment where distances and access to ambulance resources in people's immediate area are limited, other responders like firefighters, police and home healthcare nurses are available to reduce suffering and save lives when a life-threatening condition occurs (1)(2)(3)(4). Important for survival is response time, that is the interval between an emergency call to the emergency medical communication centre (EMCC) and the arrival of help at the site (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…When emergency medical dispatchers (EMDs) have access to send other responders to perform first aid before the ambulance staff arrives, an opportunity to influence the course of the situation of the affected person arises. In Sweden, there has been collaboration between counties and the municipal emergency services since the 1990s; firefighters are dispatched to perform first aid before an ambulance arrives in areas where a longer response time exists, an assignment called 'While Waiting for the Ambulance' (WWFA), (4,9). The WWFA assignment is presently in place in 260 of 290 municipalities, and this means that firefighters are educated to performing first aid using a defibrillator, to give oxygen and to increase safety until the ambulance staff arrives (10).…”
Section: Introductionmentioning
confidence: 99%
“…In order to shorten the response time, different solutions are adopted where EMCC dispatches first responders (FR) to perform life‐saving actions while awaiting the arrival of an ambulance. Primarily firefighters but also, lately, other resources are used due to their constant presence in the community, such as police officers, home health care nurses and laypersons . In Sweden, where ambulance and the fire departments (FDs) are separate organizations, firefighters are dispatched as FR on so‐called while waiting for the ambulance (WWFA) assignments .…”
Section: Introductionmentioning
confidence: 99%